The Practice of Fasting and Dhikr in Developing Emotional Spiritual Quotient (ESQ) - Ahdi, M Wafiyul; Wahyudi, Wahyudi; Islam, Ahmad Baihaqiyulloh Asy-Syadzilil (Islamic Faculty of KH. A. Wahab Hasbullah University, Jombang, Indonesia, 2024)
This study aims to explore the role of tirakat (spiritual fasting) and wirid (recitation of dhikr) as practices to develop Emotional Spiritual Quotient (ESQ). ESQ combines emotional and spiritual intelligence, aligning with Islamic principles to foster strong moral character and deeper spiritual connections. The research employs a qualitative approach to understand the phenomenon of tirakat and wirid as tools to enhance ESQ. Data collection was conducted through observations, interviews, and documentation, with data analysis using Miles and Huberman's model, consisting of data reduction, presentation, and conclusion drawing. Triangulation techniques ensured validity and reliability, including source, method, and time triangulation. The results show that tirakat and wirid significantly contribute to developing emotional and spiritual intelligence. From an emotional perspective, these practices improve self-awareness, self-regulation, motivation, and empathy. Participants demonstrated better emotional control, increased patience, and a more thoughtful response to challenges. From a spiritual perspective, tirakat and wirid cultivate sincerity (ikhlas), patience (sabar), and a stronger connection with God. Participants reported greater focus in worship, improved discipline, and a deeper sense of purpose in life. This study highlights the importance of tirakat and wirid as systematic practices for developing ESQ. By integrating these practices, individuals can cultivate emotional maturity, moral character, and spiritual intelligence, which are essential for facing life’s challenges with resilience and ethical awareness.